2004
DOI: 10.1063/1.1641146
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of excitonic recombination in lateral epitaxially overgrown InGaN/GaN quantum wells studied with cathodoluminescence

Abstract: We have examined in detail the optical properties of InGaN quantum wells ͑QWs͒ grown on pyramidal GaN mesas prepared by lateral epitaxial overgrowth ͑LEO͒ in a metalorganic chemical vapor deposition system that resulted in QWs on ͕1-101͖ facets. The effects of In migration during growth on the resulting QW thickness and composition were examined with transmission electron microscopy ͑TEM͒ and various cathodoluminescence ͑CL͒ imaging techniques, including CL wavelength imaging and activation energy imaging. Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 56 publications
3
46
0
Order By: Relevance
“…To obtain such crystal planes on high-quality c-plane GaN, we start the epitaxial growth in the c-direction, followed by the selective growth of GaN stripes with triangular crosssection. Other crystal planes form on the stripe facets, on which finally the QW structures are grown [3][4][5]. Depending on the stripe orientation and the growth conditions, different crystal facets can be obtained which all possess reduced or even zero polarization fields.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain such crystal planes on high-quality c-plane GaN, we start the epitaxial growth in the c-direction, followed by the selective growth of GaN stripes with triangular crosssection. Other crystal planes form on the stripe facets, on which finally the QW structures are grown [3][4][5]. Depending on the stripe orientation and the growth conditions, different crystal facets can be obtained which all possess reduced or even zero polarization fields.…”
Section: Introductionmentioning
confidence: 99%
“…There are several works reported on the light emission mechanism of the complicated system [12][13][14][15][16]. The emissions can be originated from the In-rich clusters and interface roughened multiple quantum wells (MQWs).…”
Section: Introductionmentioning
confidence: 99%
“…The LEDs grown with the SLs showed a PL intensity that was approximately 2.6 times higher than that of the LEDs grown without the SLs. It was reported that a decrease in dislocation density tended to enable the strong carrier localization and enhanced efficiency of radiative recombination in InGaN/GaN MQWs [20][21][22]. It was also found that the PL intensity increased with decrease in strain in the quantum wells due to the reduced piezoelectric field [23].…”
Section: Resultsmentioning
confidence: 95%